Exploring regional industrial growth: Does specialization explain it? - Leyla Ayvarovna Gamidullaeva; Elena Korostyshevskaya; Alexey Myamlin; Olga Podkorytova (Economies, 2022)
Being a form of territorial division of labor, economic specialization should be considered as a strategic management priority, contributing to a competitive territorial production structure and, consequently, regional economic growth. The article is devoted, firstly, to the development of a method for assessing the level of territorial division of labor based on a new coefficient of regional economic specialization; and secondly, to the investigation of regional specialization effects on economic growth. The purpose of the to substantiate the influence of the territory specialization factor on industrial economic growth, along with other conventional factors of regional development, using econometric methods based on an extended exogenous growth model. Premised on the data from Russian manufacturing industries and using a new coefficient of regional specialization, the authors have developed and verified an original approach to substantiate the effectiveness of regional clustering for ensuring the growth of industrial output based on an extended exogenous growth model. Approbation of the proposed assessment method and verification of research hypothesis formulated by the authors have been carried out using regional statistical data of the Russian Federation for the period from 2005 to 2019. The empirical analysis results have contributed to a place-based theoretical approach, involving both the cluster concept and the concept of 'smart specialization'. The practical significance of the research is to validate clustering feasibility as a form of territorial division of labor and provide a number of principles for the regional industrial policy based thereon to accelerate territorial economic growth.
Keywords: 330; economic growth; clusters; division of labor; industrial diversification; region; regional specialization; territory